Retórica e discurso apologético cristão em De Mortibus Persecutorum de Lactâncio: A morte dos Imperadores (Séculos III e IV d. C) - Freitas, Thiago Moreira (2024)
The present research aims to analyze the work De Mortibus Persecutorum (313-314) by Lactantius (240-320), observing the absence of funeral rituals for the deaths of the persecuting emperors. The conduct of these emperors is analyzed through their behaviors associated with poor management and governance of the empire, which, according to Lactantian perspective, resulted in tragic, undignified, and violent deaths. Thus, the character adjectives signal the political role of the emperors in Lactantius' apologetic narrative. Thus, De Mortibus Persecutorum can be characterized as an apologetic work that emphasizes the "Christian ideal" through the political and religious issues of the Late Roman Empire. From this point, this study reflects on the rhetorical devices in Lactantius' narrative and seeks to understand the different types of deaths of the persecuting emperors and their connections with Divine Providence and the legitimization of Christianity in power